The Presence in Absence: Biopsychosocial Dimensions of Prolonged Grief Disorder and the Impact of Mediumistic Sessions - Cardoso Miranda Hott, Márden (2025)
Objective: This study aimed to investigate the impact of mediumistic sessions, particularly evidential messages, on the grieving process and analyze the perceptions of mourners, medium, and collaborators involved in the event. Methodology: The research adopted a mixed-methods approach, combining qualitative and quantitative techniques, and was conducted in three phases: (1) the administration of a closed-ended questionnaire to 105 mourners in the waiting line for mediumistic sessions; (2) the administration of semi-structured questionnaires to the medium and six collaborators; (3) the administration of open-ended questionnaires to 12 mourners who received evidential messages. The quantitative analysis used descriptive and inferential statistics, while the qualitative analysis followed the Content Analysis technique. Results: The evidential mediumistic messages contributed to emotional relief and a sense of reconnection with the deceased loved ones, despite the initial discomfort in the waiting line. The perception of the medium and collaborators regarding the event's impact was positive, although the unpredictability of the messages limits the adoption of this practice as a structured therapy. Conclusion: Mediumistic sessions can play an important role in the adaptation of individuals with prolonged grief, offering spiritual comfort and promoting the re-signification of loss, highlighting the importance of integrating clinical and spiritual support.